Pseudo Meig’s syndrome- a case report - Amatya, A.; Rana, A.; Gurung, G. (Journal of Institute of Medicine Nepal, 2007)
This case concerns Pseudo-Meigs' in a 34year old lady with 3 months history of abdominal pain and distension due to ascites and pelvic mass along with massive right pleural effusion who underwent thoracocentesis and total abdominal hysterectomy with bilateral salphingooophorectomy and total omentectomy for ovarian malignancy histologically proven to be papillary adenocarcinoma with negative cytology of ascitic and pleural fluid, that resolved following tumour removal. Journal of Institute of Medicine Vol.28(1) 2006